Sedation during Imaging in Children: A Narrative Review - Agrawal, Amit; Sharma, Shweta; Shrivastava, Jyotsna (Indian Journal of Child Health, 2024)
Radiographic imaging, along with clinical signs and symptoms, go hand in hand to arrive at a diagnosis and formulate a proper treatment plan. These imaging techniques require the child to stay in one position, for a variable duration of time. The last two decades have, thus, seen an increase in procedures involving the use of sedatives in pediatric radiology. The use of sedatives ensures that the child complies throughout the procedure until the necessary data is collected. There are numerous classes of drugs used as sedatives in children, having their set of advantages and adverse effects. The need to follow a systematic protocol, proper monitoring and assessment, and selecting the drug after ruling out contraindications becomes manifold around children. This review hence, attempts to highlight the various sedative drugs in use, their adverse effects, protocols in place, and problems associated with the imaging modalities and sedative drugs in pediatric radiology.